Suffering and Care of 0–12 Year-Old Children Exposed to Intimate Partner Violence: Making Clinical Forensic Data Talk - Dessimoz Künzle, Lyne; Cattagni Kleiner, Anne; Romain-Glassey, Nathalie (Frontiers in Psychiatry, 2022)
Children’s exposure to intimate partner violence (IPV) is a widespread phenomenon that can have detrimental consequences on their health and well-being. This study examined how clinical forensic consultation data of adult victims of IPV might provide information on the potential suffering of children exposed to IPV, the duration of exposure and the knowledge of the situation by the professionals with whom those children were in contact. Data were collected from the consultation files of 112 adult victims of IPV who consulted the Violence Medical Unit at the Lausanne University Hospital (Switzerland) in 2014, and who were parents of children aged 0 through 12. Descriptive quantitative and qualitative analyses were performed. Symptoms of suffering, such as dysregulation of instinctual functions and developmental, behavioral or emotional difficulties, were reported for nearly one-third of the victims’children. Children’s exposure to IPV often started around their birth and about four in ten children had been exposed for three years or more. Health and childhood professionals were unaware of the exposure for the vast majority of the children. Clinical forensic data can be useful in providing information on the suffering and care of children exposed to IPV. Their suffering took the form of a non-specific posttraumatic symptomatology and therefore might be difficult to detect. It is necessary to make professionals and parents aware of the fact that IPV can have a harmful impact on children’s health and well-being, and to encourage health professionals to consider the possibility of IPV when facing such symptoms.